KDM4A regulates the maternal-to-zygotic transition by protecting broad H3K4me3 domains from H3K9me3 invasion in oocytes - Sankar, Aditya; Lerdrup, Mads; Manaf, Adeel; Johansen, Jens Vilstrup; Gonzalez, Javier Martin; Borup, Rehannah; Blanshard, Robert; Klungland, Arne; Hansen, Klaus; Andersen, Claus Yding; Dahl, John Arne; Helin, Kristian; et al. (Nature cell biology, 2020)
The importance of germline-inherited post-translational histone modifications on priming early mammalian development is just emerging 1 – 4 . Histone H3 lysine 9 (H3K9) trimethylation is associated with heterochromatin and gene repression during cell-fate change 5 , whereas histone H3 lysine 4 (H3K4) trimethylation marks active gene promoters 6 . Mature oocytes are transcriptionally quiescent and possess remarkably broad domains of H3K4me3 (bdH3K4me3) 1 , 2 . It is unknown which factors contribute to the maintenance of the bdH3K4me3 landscape. Lysine-specific demethylase 4A (KDM4A) demethylates H3K9me3 at promoters marked by H3K4me3 in actively transcribing somatic cells 7 . Here, we report that KDM4A-mediated H3K9me3 demethylation at bdH3K4me3 in oocytes is crucial for normal pre-implantation development and zygotic genome activation after fertilization. The loss of KDM4A in oocytes causes aberrant H3K9me3 spreading over bdH3K4me3, resulting in insufficient transcriptional activation of genes, endogenous retroviral elements and chimeric transcripts initiated from long terminal repeats during zygotic genome activation. The catalytic activity of KDM4A is essential for normal epigenetic reprogramming and pre-implantation development. Hence, KDM4A plays a crucial role in preserving the maternal epigenome integrity required for proper zygotic genome activation and transfer of developmental control to the embryo. Hoffmann and colleagues report that the mammalian maternal-to-zygotic transition requires KDM4A-mediated removal of H3K9me3 from the broad H3K4me3 domains in oocytes.